-54=a-49

Simple and best practice solution for -54=a-49 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -54=a-49 equation:


Simplifying
-54 = a + -49

Reorder the terms:
-54 = -49 + a

Solving
-54 = -49 + a

Solving for variable 'a'.

Move all terms containing a to the left, all other terms to the right.

Add '-1a' to each side of the equation.
-54 + -1a = -49 + a + -1a

Combine like terms: a + -1a = 0
-54 + -1a = -49 + 0
-54 + -1a = -49

Add '54' to each side of the equation.
-54 + 54 + -1a = -49 + 54

Combine like terms: -54 + 54 = 0
0 + -1a = -49 + 54
-1a = -49 + 54

Combine like terms: -49 + 54 = 5
-1a = 5

Divide each side by '-1'.
a = -5

Simplifying
a = -5

See similar equations:

| 72=-6m | | Log(t-3)=(17-4t) | | (3x-18)(8x+32)=0 | | .5x^4-.5=0 | | -6p=58 | | -36g+40g+19g+-47g+18g=42 | | 3(8)+2(-2)= | | 1x+3y=78 | | -29=5u+6 | | 5x+7(-x+4)=14 | | 300=15w | | 25-x=280 | | =3+(-3) | | 10x-8=6x+12 | | 4x+5.8=9x+1.8 | | 7/6z+1/3=-5/6 | | 8b-6-1=9 | | -(2+4a)+a=3a-8 | | (4x-3)+(-3x+1)= | | 2x^2+29-90=y | | 14x-3*12=x | | 2x^2+29-90=0 | | 4v-14=66 | | 0.23x=3.75+0.46 | | -3(x-4)=5 | | W-6.5= | | -7w+2.3w= | | 16-n=-26 | | 14x-3*12=1/3 | | 120+x+60+15+20= | | 17=-3k+5 | | 18500=-33x^2+1122x+12969 |

Equations solver categories